Flexible and part-time working in practice. (1st July 2019) - Sharp, Caroline
Abstract : Rising pupil numbers mean that England's schools need more teachers each year, especially in secondary schools where pupil numbers are forecast to rise by 15 per cent over the next decade. Caroline Sharp looks at how increasing part-time and flexible working opportunities could help keep teachers in the profession – and in your school…